Identification of decisive factors for greenhouse gas emissions in comparative life cycle assessments of food waste management – an analytical review - Bernstad Saraiva Schott, Anna; Wenzel, Henrik; la Cour Jansen, Jes (Journal of cleaner production, 2016)
A review of existing life cycle assessments on food waste management was made with two main aims. Firstly, to make an overview of the assessments of the global warming potential from the treatment alternatives incineration, landfill, anaerobic digestion and compost in studies reported in literature. Secondly, to identify decisive factors in general and related to system boundary settings in particular, in reviewed studies. A number of criteria were constructed for identification of relevant comparative life cycle assessments, resulting in selection of nineteen studies, containing 103 different scenarios. The systematic investigation of the studies show examples of several methodological differences as well as choices in systems boundary setting causing misleading comparisons between different treatment options, but also large variations in used input data for modeling of similar processes. The review also shows that the most significant differences in global warming results in many cases can be explained by assumptions made in relation to the background system, rather than by differences in data on emissions surging from to the foreground system. Especially assumptions on the interaction of the waste management system with the background energy system and/or bio-system were found to be decisive to the results. This highlights the importance of identification of induced and displaced marginal products in the modeling of system expansion, as well as need for increased transparency and use of sensitivity analyses related to assumptions made in background system modeling, in order to reveal under which set of assumptions results gained in the assessment are valid. •103 scenarios in comparative LCAs of organic waste management were reviewed.•Induced and displaced marginal products are decisive to the GWP-outcome.•Increased transparency and correct identification of these products are of great importance.